(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2016)
This paper aims to examine the relationships between the research of young Viktor von Weizsäcker and Kant’s critical thinking. Starting from the criticism of Driesch’s Neovitalism, here are considered some of the major contributions of Weizsacker in the years 1911-1926, in order to show its path between criticism of knowledge, metaphysics, construction of a biology and a medical anthropology.